When in Rome… A longitudinal investigation of the predictors and the development of student sojourners' host cultural behavioral engagement. (July 2021) - Serrano-Sánchez, Juan; Zimmermann, Julia; Jonkmann, Kathrin
Abstract: International educational mobility is an important instrument for immersing multicultural diversity into the thinking, feeling, and acting of young global citizens. Yet, little is known about the development of students' host-cultural behavioral engagement during a stay abroad and the individual characteristics that predict it. We adapted the theory of planned behavior to investigate the dynamic longitudinal interplay between individual predictors and students' host-cultural behavioral engagement over the course of the stay abroad. Data come from the first four waves of the project Mobility and acculturation experiences of students (MAPS; N = 1, 225). Results confirmed the influence of acculturation attitudes, subjective norms, and multicultural self-efficacy on host-cultural behavioral engagement over time. Simultaneously, host-cultural behavioral engagement was identified as a relevant predictor of adolescents' individual development abroad.